Estudio de factibilidad para la implementación de una fábrica procesadora de chifle artesanal en el Cantón Buena Fe. - Silva Sánchez, Nexar Rolando (2019)
Plantain cultivation in Ecuador has become an essential product for food and production, there are several ways to consume it, and one of them is the production of chifle. The objective of this project is to determine the feasibility for the creation of an artisanal chifle processing factory in Canton Buena Fe, focused on the internal and external commercialization of chifles, for which a market study was carried out, considering the technical aspect and financial. Of the problems, there is little production of artisanal chifles, the reason why they do not have a local company dedicated to the processing of chifles. The lack of production of local handmade chifles, has led merchants to be forced to acquire the product in other areas near the canton, such as Quevedo and Santo Domingo. Based on this problem, the feasibility was determined for the implementation of a production and marketing factory of artisanal chifles. Of the methodology, this research is qualitative and quantitative because the data was studied and analyzed throughout the study process, the survey was applied to the people and merchants of the Buena Fe canton, to obtain data to verify the demand, this being high, with 70% of consumption. With the chifle that comes from the manufacturer and its distribution employ people for delivery to all the premises at a similar price of 0.50 cents. The technical and financial study ensures the viability of the implementation project of the artisan factory of chifles, and the unsatisfied demand borders the 7540 to 9185 cases. Net Present Value (VAN) ensures that in the third year the investment is recovered and the Internal Rate of Return (TIR) reaches 31.17% which confirms the feasibility and viability of the project. Keywords: Feasibility, commercialization, supply, demand, chifles